Mangrove Community Structure In Mesjid Lama Village, Talawi District, Batu Bara District, North Sumatra Province - Simamora, Ronita Haulian; Handoco, Ewin; , welmar Olfan Basten Barat (Sam Ratulangi University, 2024)
Mangroves are ecosystems in intertidal areas with strong interaction between marine, brackish, river, and terrestrial waters. Mangrove forests are one of the natural resources of coastal areas which have an important role in ecology, economy, and social aspects. The main benefit of mangroves is balancing the ecosystem and providing various life needs for humans and other living creatures. Besides being known to have economic potential as a provider of wood resources, fishing, crabs, and so on, mangrove forest resources also play a role in preventing sea waves and seawater intrusion towards land. The research location is in Mesjid Lama Village, Talawi District, Batu Bara Regency, North Sumatra Province. Mangrove observations used the quadrant transect method, where this research analyzed the types of mangroves, diversity, uniformity of mangroves, dominance, and INP of mangroves, and canopy cover. Three species of mangroves were found in Mesjid Lama Village, Talawi District, Batu Bara Regency, namely Avicenia Officinalis, Bruguiera cylindrica, and Rhizophora apiculata. Keywords: Mangrove Ecosystem, Diversity, Uniformity, Dominance, Importance Value Index, Mangrove Canopy Cover. Abstrak Mangrove merupakan ekosistem yang berada pada wilayah intertidal dimana pada wilayah tersebut terjadi interaksi yang kuat antara perairan laut, payau, sungai dan terestrial. Hutan mangrove merupakan salah satu sumberdaya alam wilayah pesisir yang memiliki peranan penting dari segi ekologi, ekonomi, dan social nya. Manfaat utama mangrove sebagai penyeimbang ekosistem dan penyedia berbagai kebutuhan hidup bagi manusia dan makhluk hidup lainnya. Sumberdaya hutan mangrove, selain dikenal memiliki potensi ekonomi sebagai penyedia sumberdaya kayu, penangkapan ikan, kepiting dan lain - lain, juga berperan untuk menahan gelombang laut dan intrusi air laut ke arah darat. Lokasi penelitian berada di Desa Mesjid Lama Kecamatan Talawi Kabupaten Batu bara Sumatera Utara, Pengamatan mangrove menggunakan metode transek kuadran, dimana penelitian ini menganalisis jenis – jenis mangrove, Keanekaragaman dan keseragaman mangrove, Dominansi dan INP mangrove serta Tutupan kanopi. Jenis mangrove di Desa Mesjid Lama Kecamatan Talawi Kabupaten Batu bara ditemukan 3 spesies yaitu Avicenia oficinalis, Bruguiera cylindrica, dan Rhizophora apiculata. Kata Kunci : Mangrove, Keanekaragaman dan Keseragaman, Dominansi, Indeks Nilai Penting, Tutupan Kanopi.